2012
DOI: 10.1089/fpd.2012.1267
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characterization of Extended-Spectrum Beta-Lactamase (ESBL)– and CMY-2–ProducingEscherichia coliIsolates from Healthy Food-Producing Animals in Tunisia

Abstract: The prevalence of extended-spectrum beta-lactamase (ESBL)- and plasmidic AmpC-beta-lactamase (pAmpC-BL)-producing Escherichia coli isolates has been studied in food-producing animals at the farm level in Tunisia, and recovered isolates were characterized for the presence of other resistance genes and integrons. Eighty fecal samples of food-producing animals (23 sheep, 22 chickens, 22 cattle, six horses, five rabbits, and two dromedaries) were obtained from 35 different farms in Tunisia in 2011. Samples were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 38 publications
9
54
0
Order By: Relevance
“…In the Netherlands, Overdevest et al (2011) and Leversteinvan Hall et al (2011) reported 80 and 94% prevalence of ESBLs-producing E. coli in chicken meat and raw meat, respectively. Escudero et al (2010), Schmid et al (2013), Adenaike et al (2013), Ben Sallem et al (2012) and Guandong and Avci (2013) reported 72, 21.4, 45, 13.8 and 44.4% prevalence of ESBL-producing E. coli from pigs in Spain, beef cattle in Germany, roasted beef in Nigeria, foodproducing animals in Tunisia and food of animal origin in Turkey, respectively. The isolation prevalence of ESBLresistant E. coli (8.7%) in this study is lower when compared with those of the previous studies.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…In the Netherlands, Overdevest et al (2011) and Leversteinvan Hall et al (2011) reported 80 and 94% prevalence of ESBLs-producing E. coli in chicken meat and raw meat, respectively. Escudero et al (2010), Schmid et al (2013), Adenaike et al (2013), Ben Sallem et al (2012) and Guandong and Avci (2013) reported 72, 21.4, 45, 13.8 and 44.4% prevalence of ESBL-producing E. coli from pigs in Spain, beef cattle in Germany, roasted beef in Nigeria, foodproducing animals in Tunisia and food of animal origin in Turkey, respectively. The isolation prevalence of ESBLresistant E. coli (8.7%) in this study is lower when compared with those of the previous studies.…”
Section: Discussionmentioning
confidence: 98%
“…AmpC cephalosporinases mediate resistance to 3 rd -generation β-lactams/cephalosporins, but are not inhibited by clavulanic acid and other β-lactamase inhibitors (such as sulbactam and tazobactam) (Ben Sallem et al, 2012). Conversely, the ESBLs are inhibited by clavulanic acid and other β-lactamase inhibitors (GarciaGraells et al, 2010;Ben Sallem et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…coli isolated from animals with multiple antibiotic-resistant phenotypes have been reported in Tunisia and worldwide [13,14]. This situation has resulted in a need for more epidemiological information on the prevalence of resistance to various antibiotics and their relevant genes, such as virulence gene combinations in animal isolates.…”
Section: Introductionmentioning
confidence: 99%